Contra os moralistas: contrapontos a quatro leituras de viés moral da arte retórica de Aristóteles - Marques, Saulo Bandeira de Oliveira (2019)
Probably due to her instrumentality, there is a general disquiet when dealing with rhetoric, often reputed to be an immoral practice. This image accompanies her since its dispute against the philosophy by the primacy of being the paideía, in Hellas of 5th century BC. However, at that time, there were already some perspectives that moved away, in whole or in part, from this perception. For example, Aristotle wrote an Art of Rhetoric with the purpose of to offer a technical treatment to rhetoric, exhorting to exercise it through its moral bias. His admonition still today leads to interpretations of rhetoric as a moral activity, under several grounds, notwithstanding his technical nature to point at an ambivalence in this sphere. From this perspective, those moral readings are considered as partial readings, whether because of their incompleteness or because of their unidirectionality, therefore they are inadequate to characterize rhetoric. In this sense, and in opposition to such perspectives, the rhetoric is presented as a derivation of deinotēs, advocating for a primarily ambivalent bias in the moral sphere. In order to do so, four moral bias readings with different representative grounds were examined through the Toulmin model of argumentation, from which has been extracted the elements to elaborate of the counterargument by the rhetorical technique of inventio by antimodel. Once their support grounds were unveiled, it’s possible verify these rebuttals as an equivalent perspectives, rejected as such by a limited view of the functions of rhetoric. Hence, the reading of rhetoric as deinotēs is the most consistent with her technical nature: as art, the rhetoric is neither virtue nor cunning; but a “reason” of contingent, a skill of the practical judgment which, by observing the surrounding reality in its task of “finding the most pertinent means to persuade” (Rhetoric, 1355b25-26), aid to speculate and act in the World.